THE PEDAGOGICAL ACTIVITY OF MUNAVVAR QORI ABDURASHIDKHANOV AND HIS ROLE IN THE FORMATION OF THE NATIONAL HIGHER EDUCATION SYSTEM - Sevinch Ismatullayeva (International Journal of Literature and Language Studies, 2026)
This article scientifically analyzes the role of Munavvar qori Abdurashidkhanov in the formation of the national higher education system and his enlightening activities within the framework of the Jadid movement. In particular, his views on developing new methods of education, combining modern knowledge with national values, and establishing a three-tier national education system are highlighted.